The effects of supplementing roughage diets with leguminous tree forages on intake, digestion and performance of crossbred cattle in Coastal lowland Kenya. - Abdulrazak, S.A. (University of Aberdeen, 1995)
Chapter One. A general introduction on feed resources in the coastal lowland Kenya, use of the legume tree forages, and their effect when used as supplements to low quality roughage is presented. This is followed by a review of the literature on the role of microbes in the rumen and the synthesis of microbial protein. The factors that influence the feed intake in ruminants are also reviewed. The role of the leguminous tree forages as supplements to low quality basal diet is presented with more emphasis on the effects of feeding forages from gliricidia and leucaena trees, on intake, digestion and animal productivity. The effects of deleterious compounds with particular reference to tannin is reviewed. Chapter Two. Twenty intact and five fistulated crossbred steers (Ayrshire/Brown Swiss x Sahiwal) were used in Experiment One. The materials and methods used in this experiment had much in common with those of the three following experiments. Therefore procedures similar to all experiments are described in this chapter and only briefly mentioned in the subsequent chapters. The objective of the experiment was to describe the response in production as a result of supplementing napier grass basal diet with incremental levels of gliricidia forage. Napier grass basal diet was offered ad libitum alone or supplemented with 7.5, 15, 22.5 or 30 g DM/kg W0.75/d. Intake and live weight changes were measured for 49 days, and digestibility, and microbial N supply during the last week of the experiment with the twenty steers, in a randomized design. The rumen parameters were measured in the five fistulated steers in a 5 x 5 latin square design. Total Dry matter (DM) intake tended to increase (5.2, 5.1, 5.2, 5.4 and 5.7 kg DM/d, s.e.d 0.21; P 0.05) with supplementation, but this was accompanied by a linear decrease in napier grass intake (5.2, 4.7, 4.5, 4.3 and 4.2 kg DM/d, s.e.d 0.21; P 0.05). The diet digestibility, rumen pH and in sacco DM degradation of napier grass remained unchanged, while the rumen ammonia concentrations (NH3-N) were increased linearly (P 0.05) from 130 to 215 mg/1 for control and highest level of gliricidia forage offered. When gliricidia was offered as proportionally 0.26 of the diet, animal weight gains were increased proportionally by about 0.56. The relationship between the amount of gliricidia offered and the average daily gain was such that, every 10 g DM /kg W0-75 increment of gliricidia forage resulted in 49 g/d of live weight gain. The estimated microbial N supply were lowest in the control group and supplementation tended to increase the yield, but with no significant difference across the treatments. Chapter Three. The objective of Experiment Two was to examine the effect of supplementing napier grass with incremental levels of leucaena forage on voluntary food intake, diet digestibility, rumen fermentation, and live weight gains in steers. The same animals used in Experiment One were used in this experiment. The levels of leucaena offered were 0, 7.5, 15, 22.5 or 30 gDM/kg W0.75/d, the same as those of gliricidia in Experiment One. Increasing the proportion of leucaena forage in the diet of steers offered napier grass had no significant effect on the intake of the napier grass (5.2, 5.3, 5.3, 5.3 and 5.0 kg DM/d, s.e.d. 0.21). The total DM intake increased linearly (5.2, 5.8,6.2,6.6 and 6.7 kg DM/d, s.e.d 0.31; P 0.001). The response was such that for every increment of 10 g DM/kg W0.75 of leucaena, the total intake was increased by 0.52 kg DM/d. Diet digestibility tended to increase, while the rumen pH and in sacco DM degradation characteristics remained unchanged with supplementation. Rumen NH3-N was significantly increased by approximately 11 mg/1 for every 10 g DM/kg W0.75/d of leucaena forage offered. The growth of the animals was improved with supplementation, and the relationship between the amount of leucaena in the diet and the gain was such that for every 10 g DM/kg W0-75/d increment of leucaena forage intake, the gains were increased by 96 g/d. It could be predicted that 1 kg of leucaena offered would result in 171 g/d of gain. At a highest level of leucaena offered ie. proportionally 0.27 of the diet, the weight gains were increased by 0.57 compared with the control group. Chapter Four. The objective of Experiment Three was to examine the effect of incremental levels of gliricidia forage on voluntary food intake, digestion, microbial N supply and live weight gains. Twenty crossbred steers (Ayrshire/Brown Swiss x Sahiwal) and five fistulated steers of the same breed were used for the trial. Intake, diet digestibility, microbial N supply and live- weight changes were measured using the twenty steers and the rumen parameters using the five fistulated steers. Maize stover was offered ad libitum plus 1 kg of maize bran alone, or supplemented with 7.5, 15, 22.5 or 30 g DM/kg W0.75/d of gliricidia forage. Supplementation with gliricidia forage significantly increased the total DM intake (3.0, 3.0, 3.2, 3.5, 3.5 kg DM/d, s.e.d. 0.10; P 0.001) but depressed the intake of maize stover. The response in total DMI was an additional of 0.21 kg DM/d for an increment of 10 g DM/kg W0.75 of the legume. Diet digestibility was not significantly changed, nor was the rumen pH. The degradation parameters was slightly higher in the supplemented group, however, there were no difference in the degradation characteristics of the feeds incubated in steers offered different level of legume forage. Rumen NH3-N and live weight gains were significantly increased with supplementation. The relationship between the proportion of the supplement in the diet and the rumen ammonia or daily gains were such that, for every increment of 10 g DM/kg W0 75 of the legume offered the NH3-N and daily gain were increased by 16 mg/1 and 69 g/d respectively. The microbial N supply tended to be higher in the supplemented groups than the control (30.8, 37.2, 32.9, 34.9, 32.3, s.e.d. 1.06; P 0.05). Chapter Five. Experiment Four compared the type (gliricidia or leucaena) and levels (15 or 30 g DM/kg W0.75) of legume forages given as supplements to maize stover. The effects on intake, diet digestibility, rumen parameters, microbial N supply and live weight gains are presented and discussed. The same steers used in Experiment Three were used in this experiment (Twenty for the growth trial, and the five fistulated animals for the measurements of rumen parameters. The steers were offered maize stover ad libitum plus 1 kg maize bran alone, (2 kg for the fistulated animals), or supplemented with either 15 or 30 g DM/kg W0.75/d of gliricidia or leucaena (Control, G15, G30, L15 or L30). The intake of the basal diet was significantly (P 0.05) increased from 2.3 to 2.5 and 2.3 to 2.7 kg DM/d when of either gliricidia or leucaena respectively were offered as 0.17 of the diet. At higher level of supplementation (to about 0.33 of diet), the maize stover intake tended to decline. The total DM intake were increased (P 0.001) at both levels of both supplements offered (3.2,4.1,4.6,4.3 and 4.6 DM/kg, s.e.d 0.05, being the intakes for control, G15, G30, L15 and L30 respectively). Supplementation at the lower level significantly increased the diet digestibility. The rumen pH remained unchanged, the rumen NH3-N increased (31, 80, 101, 95, 111 mg/1 s.e.d 20.4; P 0.001), and the in sacco DM characteristics of the feeds tended to increase with supplementation. Both the DM and nitrogen (N) in leucaena forage were degraded at a slower rate than in gliricidia. The control group had the lowest (P 0.001) gains, compared with the supplemented groups. The leucaena supplemented group tended to have higher live weight gains than the gliricidia group, but the differences were not significant. Gains were 81, 355, 695, 396, 753 g/d s.e.d 44.5 for control, G15, G30, L15 and L30 groups respectively. With all parameters measured, there were no significant difference between supplementation with gliricidia or leucaena forages, at either level.